ENVIRONMENTAL PROTECTION AND STATE RESPONSIBILITY IN INTERNATIONAL HUMANITARIAN LAW - Afriansyah, Arie (Indonesian Journal of International Law, 2021)
International armed conflicts is not only threatened the existence of human being, but also brought great environmental damage that has served to raise the international community's deep concern. The conflicting parties are liable for violations of their international obligations including damages to the environment. The obligations of warring parties to protect the environment are sourced not only from treaty law but also from customary law. Even though the conflict has ceased, they are still liable for the violations as long as the damages continue. That is why the legal concept of State offers an important doctrine in international conflicts offering the basis of reparation for damaged environment which needing prompt action to be taken by the responsible State.